Upaya Eks-Orang dengan Gangguan Jiwa dalam Menghadapi Stigma Sosial (Studi Kasus di Kabupaten Bondowoso) - Andawiyah Nurin Sabiela (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
People who have recovered from mental disorders still experience social stigma in the community. This stigma appears in a form that impacts the lives of former ex-ODGJ. This condition causes ex-ODGJ to experience difficulties in carrying out their social functions such as obtaining employment and re-interacting with society. Based on the data obtained, of the 23 ex-ODGJ identified as experiencing social stigma, there were 5 ex-ODGJ who were able to survive and continue to carry out their social functions despite still experiencing stigma from the community. Therefore, this study aims to determine what efforts are made by ex-ODGJ in dealing with social stigma. This study uses a qualitative approach with a case study research type. The research location was carried out in Bondowoso Regency. The determination of informants used a purposive sampling technique consisting of five main informants and six additional informants. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the Miles, Huberman, and Saldana model which includes data condensation, data display, and drawing and verifying conclusions. Data validity was tested through source triangulation and technical triangulation. The research results show that the social stigma experienced by ex-ODGJ still occurs in various negative labels, stereotypes, separation, and discrimination. This stigma causes ex-ODGJ to experience a lack of self-confidence, withdrawal from their environment, and obstacles in obtaining employment. However, ex-ODGJ make various efforts to overcome social stigma, namely self-advocacy, perseverance in starting a business, participation in community activities, fulfillment of self-actualization, and participation in religious activities in the community. These efforts are carried out as a form of recovery and self-prove that ex-ODGJ are able to be productive and return to their social function in society.
Approved by Teddy
Keywords: ex-ODGJ; social stigma; social functioning; efforts to address stigma.